Research on control logic of anti-lock braking system of pure electric smart car - Liu Bin; Shi Wei; Chang Jiawei; Li Zhanfeng (Dianzi Jishu Yingyong, 2022)
Brake-by-wire technology is one of the key technologies of pure electric smart cars. In order to improve the safety and stability of automobile braking, it is necessary to study the control logic of the anti-lock braking system of a pure electric smart car. Before the implementation of this program, a reasonable logic threshold is set for simulation experiments. In this paper, a vehicle dynamics model with 8 degrees of freedom is built based on Simulink to simulate the braking conditions in a curve, and the differential control of the vehicle is realized by controlling the yaw moment of the vehicle. Through simulation experiments, the rationality of the proposed anti-lock braking system control logic is verified, which has guiding significance for the subsequent research and development of brake-by-wire systems.